Towards antiviral polymer composites to combat COVID‐19 transmission. Issue 11 (4th May 2021) - Mouritz, Adrian P.; Galos, Joel; Linklater, Denver P.; Ladani, Raj B.; Kandare, Everson; Crawford, Russell J.; Ivanova, Elena P.
Abstract: Polymer matrix composite materials have the capacity to aid the indirect transmission of viral diseases. Published research shows that respiratory viruses, including severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2 or COVID‐19), can attach to polymer substrata as a result of being contacted by airborne droplets resulting from infected people sneezing or coughing in close proximity. Polymer matrix composites are used to produce a wide range of products that are "high‐touch" surfaces, such as sporting goods, laptop computers and household fittings, and these surfaces can be readily contaminated by pathogens. This article reviews published research on the retention of SARS‐CoV‐2 and other virus types on plastics. The factors controlling the viral retention time on plastic surfaces are examined and the implications for viral retention on polymer composite materials are discussed. Potential strategies that can be used to impart antiviral properties to polymer composite surfaces are evaluated. These strategies include modification of the surface composition with biocidal agents (e.g., antiviral polymers and nanoparticles) and surface nanotexturing. The potential application of these surface modification strategies in the creation of antiviral polymer composite surfaces is discussed, which opens up an exciting new field of research for composite materials. Abstract : Polymer matrix composites are used to produce a wide range of products that are "high‐touch" surfaces, such as sporting goods, laptop computers and household fittings, and these surfaces can be readily contaminated by pathogens. Factors controlling the viral retention time on plastic surfaces including SARS‐CoV‐2 (COVID‐19) are examined and the implications for viral retention on polymer composite materials are discussed. Potential strategies that can be used to impart antiviral properties to polymer composite surfaces are evaluated.